Knowledge, attitude and perception of contraception among medical students in Universiti Putra Malaysia - Ma, Saung Oo; Marzuki, Nursyahirah; Wei, Rou Ean; Abdul Hamid, Habibah; Affendi, Nik Rafiza (Malaysian Public Health Physicians' Association, 2019)
The incidence of unintended pregnancy and unsafe abortion are significantly high due to the lack of knowledge and negative attitude towards contraception and it can be prevented by effective and appropriate contraceptive knowledge and usage. Considering the future role of medical students as family planning educator as well as counsellors, it is not only important to determine their knowledge, attitude and perception towards contraception but also should be updated for improvement on the quality of future healthcare professionals on contraceptive knowledge which may lead to the reduction in the number of unintended pregnancy with improving maternal morbidity and mortality. This was a cross sectional study using self-reported questionnaires survey that consists of four sections as socio-demographic characteristics information, knowledge towards contraception, attitude towards contraception, and perception of education and training in sexual and reproductive health among medical student. Questions were, distributed among medical students in Faculty of Medicine and Health Sciences and analyzed. The response rate was 100%. and most of the respondents in this study were Malay (64·4%), female (68·3%), single (98·6%) and live in urban area (69·1%). Most of their parents had tertiary education level (father educational level, 63·3%; mother educational level, 50·0%). 56·1% of the respondents had poor level of knowledge and 59.2% of them had negative attitude towards contraception. Regarding the perception on contraception, most of the respondents thought that they did not have sufficient clinical practice (50·4%) though adequate training (57·6%) in counselling the patients for family planning service during their clinical posting. There was a significant association between gender, place of birth, ethnicity, marital status, father educational status and level of knowledge. There were a higher percentage of respondents who had poor knowledge and negative attitude towards contraception. Assessing the knowledge and attitude of medical students on contraception and their relationship with socio-demographic characteristics and socio-economic factors plays a leading role in public health projects which are aimed to combat maternal mortality through reducing unintended pregnancies. To change the attitude towards contraception and further increase the level of knowledge of contraception among medical students, collaborated health education and similar studies among health workers are highly recommended.